Transfer of Function of Waqf Land Analysis of Law Number 41 of 2004 - Thuwaiba, Thuwaiba; Habiburrahman, Muhammad; Isma Putri, Cici (Samara: Journal of Islamic Law and Family Studies, 2025)
This article was written based on the discovery that there was waqf land that was originally built as a prayer room. The waqf land was located on a hill. However, the prayer room that had been built was demolished by the waqf's grandson and moved to another location. A house was built on the site of the demolished prayer room. The author used qualitative research methods, employing descriptive methods. The data collection tools were observation, interviews, and documentation. Since this study analyzed the transfer of waqf land functions based on Law No. 41 of 2004, the author used a normative legal and empirical legal approach in this paper. From the research findings, it can be concluded that first, the views of the surrounding community regarding the conversion of waqf land indicate that some members of the community are unaware of the laws governing waqf land. This suggests that the community's understanding of waqf land is still limited, as evidenced by some members of the community converting the function of waqf land. Second, the waqf land was originally built as a mosque. The location of the endowment land is on a hill, but the mosque that had been built was demolished by the endower's grandchild and relocated to another place. The site of the demolished mosque was then built into a house by the endower's grandchild. Third, an analysis of Law No. 41 of 2004 on the conversion of the function of waqf land states that waqf land that has been donated as waqf is prohibited from being changed in status or transferred in any form except through an exchange intended for public interest in accordance with the general spatial plan outlined in Law No. 41 of 2004 on Waqf, Articles 1 and 2.